2000
DOI: 10.1038/sj.ijo.0801426
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, physical inactivity and low level of physical fitness as determinants of all-cause and cardiovascular disease mortality—16 y follow-up of middle-aged and elderly men and women

Abstract: OBJECTIVE: To investigate the independent associations and the possible interaction of body mass index (BMI), leisure time physical activity (LTPA) and perceived physical ®tness and functional capability with the risk of mortality. DESIGN: Prospective 16 y follow-up study. SUBJECTS: A regionally representative cohort of 35 ± 63 -y-old Finnish men (n 1090) and women (n 1122). MEASUREMENTS: All-cause, cardiovascular disease (CVD) and coronary heart disease (CHD) mortality were derived from the national census da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
93
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 42 publications
3
93
0
7
Order By: Relevance
“…Other studies that have validated self-reported weight or height, however, have found strong correlations with measured values. 5,14,44 Nonetheless, it is likely that heavy participants under-reported their weight, leading to some overestimating of risks at lower BMI categories. Data on BMI was missing on less than 3% of the study population who were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that have validated self-reported weight or height, however, have found strong correlations with measured values. 5,14,44 Nonetheless, it is likely that heavy participants under-reported their weight, leading to some overestimating of risks at lower BMI categories. Data on BMI was missing on less than 3% of the study population who were excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many prospective epidemiologic studies have evaluated the relationship between mortality and body mass index (BMI) (weight adjusted for height (kg/m 2 )), [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] which is commonly considered a surrogate for body fat. Study findings vary as to whether the relationship is best described as direct, J-or U-shaped, the latter two characterizations suggesting higher risks among both heavier and leaner individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown an inconsistent relationship between body mass index (BMI) and mortality risk, with associations being J-or U-shaped [4][5][6][7][8][9][10][11][12], direct linear [13][14][15][16] or absent [17,18]. This could be due to the inadequate control for smoking status and pre-existing chronic diseases, both of which are associated with a low BMI and an increased risk of death [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several, but not all, previous studies have reported a curvilinear association between body weight and mortality, in which the risk is increased among both the leanest and the heaviest persons. 10,[14][15][16][17][18][19][20][21] In most studies, the increased risk in the leanest individuals attenuated or even disappeared after excluding smokers or subjects with pre-existing diseases.…”
Section: Introductionmentioning
confidence: 99%